2021
DOI: 10.1021/acsabm.0c01431
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitive Detection of Anions in Pure Organic and Aqueous Media by Amino Acid Conjugated Ellman’s Reagent

Abstract: The last few decades witnessed a remarkable advancement in the field of molecular anion receptors. A variety of anion binding motifs have been discovered, and large number of designer molecular anion receptors with high selectivity are being reported. However, anion detection in an aqueous medium is still a formidable challenge as evident from only a miniscule of synthetic systems available in the literature. We, herein, report 5,5′-dithio-bis­(2-nitrobenzoic acid) (Ellman’s reagent) appended with amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The peaks at E pa = −0.57 V and E pc = −0.81 V represent the redox couples Ni­(II)/Ni­(I) and Ni­(I)/Ni­(II), respectively, whereas the peaks at E pa = 0.41 V and E pc = −1.61 V indicate the redox couples Ni­(III)/Ni­(I) and Ni­(I)/Ni­(III), respectively. , This observation suggested the in situ Ni­(II) complexation of the conjugate base of S1 , which is formed upon the deprotonation reaction with fluoride. However, S2 did not show any significant response for aqueous sodium fluoride even in the presence of Ni­(II) ions. , …”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The peaks at E pa = −0.57 V and E pc = −0.81 V represent the redox couples Ni­(II)/Ni­(I) and Ni­(I)/Ni­(II), respectively, whereas the peaks at E pa = 0.41 V and E pc = −1.61 V indicate the redox couples Ni­(III)/Ni­(I) and Ni­(I)/Ni­(III), respectively. , This observation suggested the in situ Ni­(II) complexation of the conjugate base of S1 , which is formed upon the deprotonation reaction with fluoride. However, S2 did not show any significant response for aqueous sodium fluoride even in the presence of Ni­(II) ions. , …”
Section: Resultsmentioning
confidence: 79%
“…However, S2 did not show any significant response for aqueous sodium fluoride even in the presence of Ni(II) ions. 55,56 Furthermore, the electrochemical response of S1 upon incremental addition of aqueous fluoride ions in the presence 57,58 The study also revealed that the acetate anion led to some responses similar to that of the fluoride anion but with lower intensity. However, comparatively lower basic anions like Cl − , I − , HSO 4 − , and H 2 PO 4 − did not show any significant effect on the DPV pattern (Figure S47).…”
Section: Elucidation Of the Fluoride Recognition Mechanismmentioning
confidence: 85%
See 1 more Smart Citation
“…The sensing and recognition of anions have garnered an increasing level of attention in light of the essential roles they play. 1,2 Cyanide specifically refers to compounds containing a cyano group (CN − ), which encompasses hydrogen cyanide, sodium cyanide, potassium cyanide, and ammonium cyanide. 3,4 Most inorganic cyanides are extremely toxic.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Recently, among various bio-inspired materials, peptides and pseudopeptides have drawn significant attention due to their biocompatibility, molecular recognition (e.g., H-bonding and electrostatic interactions), and electronic properties. [18,[22][23][24][25][26][27] Nguyen et al demonstrated excellent piezoelectric properties of self-assembled peptide microrods, which could generate opencircuit output voltages up to ≈1.4 V. [22] Lee et al reported aligned peptide nanorods with improved piezoelectric properties and output voltages up to ≈2.8 V. [28] Hence, owing to their biocompatibility, intrinsic self-assembling ability, and piezoelectric properties, peptide-based materials are efficient candidates to be used as fillers in the PVDF matrix.…”
Section: Introductionmentioning
confidence: 99%